(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the importance of differential equations in developing intuitive competence among cadets of higher military educational institutions. Using a scientific-methodological approach, the study analyzes how differential-equation-based modeling supports rapid decision-making, situational assessment, forecasting, and the optimization of tactical and technical actions in complex military environments. The pedagogical mechanisms for enhancing intuitive thinking are explained, supported by real military modelling examples.